Analysis of childbirth care practices in a public maternity hospital - Maria Aline Rodrigues Barros; Luana Silva de Sousa; Camila Félix Américo; Cinthia Maria Gomes da Costa Escoto Esteche; Ana Kelve de Castro Damasceno; Flávia Ximenes Vasconcelos (Universidade Federal do Ceará, 2019)
Objective: to analyze childbirth and birth care practices in a public maternity hospital. Methods: a cross-sectional descriptive study made in a tertiary maternity hospital with 264 puerperal women. Collection proceeded by means of a form based on good childbirth care practices. Results: prevalence of good childbirth care practices. It was observed that 233 (88.3%) received information, 256 (97.0%) had freedom of position, fetal monitoring occurred in 260 (98.5%), 198 (75.0%) used non-pharmacological pain relief methods, 263 (99.6%) were entitled to a companion, skin-to-skin contact in 258 (98.1%). Conclusion: practices such as early amniotomy and repeated touches were found that should be used with caution. In addition, the use of the Kristeller maneuver was verified, although in a low percentage, which should be eliminated from delivery care.